Discovery of a nucleocytoplasmic O-mannose glycoproteome in yeast - Halim, Adnan; Neubert, Patrick; Strahl, Sabine (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Dynamic cycling of N-Acetylglucosamine (GlcNAc) on serine and threonine residues (O-GlcNAcylation) is an essential process in all eukaryotic cells except yeast, including Saccharomyces cerevisiae and Schizosaccharomyces pombe. O-GlcNAcylation modulates signaling and cellular processes in an intricate interplay with protein phosphorylation and serves as a key sensor of nutrients by linking the hexosamine biosynthetic pathway to cellular signaling. A longstanding conundrum has been how yeast survives without O-GlcNAcylation in light of its similar phosphorylation signaling system. We previously developed a sensitive lectin enrichment and mass spectrometry workflow for identification of the human O-linked mannose (O-Man) glycoproteome and used this to identify a pleothora of O-Man glycoproteins in human cell lines including the large family of cadherins and protocadherins. Here, we applied the workflow to yeast with the aim to characterize the yeast O-Man glycoproteome, and in doing so, we discovered hitherto unknown O-Man glycosites on nuclear, cytoplasmic, and mitochondrial proteins in S. cerevisiae and S. pombe. Such O-Man glycoproteins were not found in our analysis of human cell lines. However, the type of yeast O-Man nucleocytoplasmic proteins and the localization of identified O-Man residues mirror that of the O-GlcNAc glycoproteome found in other eukaryotic cells, indicating that the two different types of O-glycosylations serve the same important biological functions. The discovery opens for exploration of the enzymatic machinery that is predicted to regulate the nucleocytoplasmic O-Man glycosylations. It is likely that manipulation of this type of O-Man glycosylation will have wide applications for yeast bioprocessing.
Gesehen am TT.MM.JJJ